Tracer Study Terhadap Respon Stakeholder untuk Evaluasi dan Pengembangan Kurikulum Program Studi - Resi Pratiwi; Atik Rahmawati (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2020)
This study aimed to determine the graduate user assessment (stakeholder response). The method used is through a preliminary survey phase of the alumni database, creating a google form tracer study of stakeholder responses, tracking stakeholder responses, distributing tracer study questionnaires and random stakeholder interviews. The research sample is the 2012-2014 class of chemistry graduate users who have been recorded in a tracer study of aspects of alumni tracking. The results of the study show that the assessment of graduates according to stakeholders is integrity (moral and ethics) very good category (63%), professionalism is good (51%), information technology is good (61%), teamwork is good (aspects) 63%), good personal development aspects (63%), good leadership aspects (80%), good foreign language skills (68%), good communication skills (73%), innovation ability and creativity good category (59%), and motivation in working good category (51%).